The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/chem.201801804
|View full text |Cite
|
Sign up to set email alerts
|

Switchable Synthesis of Z‐Homoallylic Boronates and E‐Allylic Boronates by Enantioselective Copper‐Catalyzed 1,6‐Boration

Abstract: The enantioselective Cu-catalyzed 1,6-boration of (E,E)-α,β,γ,δ-unsaturated ketones is described, which gives homoallylic boronates with high enantiomeric purity and unexpectedly high Z-selectivity. By changing the solvent, the outcome can be altered to give E-allylic boronates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…The Meek group found that vinylboronates could serve as precursors to hydroxy bis(boronates) (Scheme 61). 158 The syn-diastereomer underwent elimination during silica gel chromatography, affording exclusively the anti-diastereomer (241). The products were obtained in good yields and enantioselectivities with a variety of aryl, alkyl, and alkenyl aldehydes, although the intermolecular variant was only explored with vinylboronate (239).…”
Section: Ketones/aldehydesmentioning
confidence: 99%
“…The Meek group found that vinylboronates could serve as precursors to hydroxy bis(boronates) (Scheme 61). 158 The syn-diastereomer underwent elimination during silica gel chromatography, affording exclusively the anti-diastereomer (241). The products were obtained in good yields and enantioselectivities with a variety of aryl, alkyl, and alkenyl aldehydes, although the intermolecular variant was only explored with vinylboronate (239).…”
Section: Ketones/aldehydesmentioning
confidence: 99%
“…47 The utility of the reaction was further examined on linear and cyclic aliphatic aldehydes with increased base loading, generating the desired products 34-35 in lower yields. For the conjugated electrophile, both electron-withdrawing and donating groups on the aryl ketone provided the desired 1,6addition products in moderate to good yields (36)(37)(38)(39)(40)(41)(42)(43). The thiophene-derived heteroarene ketone also led to a moderate yield (44).…”
Section: Resultsmentioning
confidence: 99%
“…31,32 Alternative transition-metal catalyzed 1,6-additions have been developed by Hayashi with rhodium, 11 cobalt, 33 and iridium catalysts. 34,35 Expansion of metal-catalyzed 1,6-additions to boryl and silyl groups are represented by the works of Lam, 36,37 Liao 38 and Newhouse. 39 While these advancements are very signicant, most involve stoichiometric use of organometallic nucleophiles, which inevitably leads to sizable metallic waste and poor atom economy.…”
Section: Introductionmentioning
confidence: 99%
“…The similar reaction tendency was also observed in the copper(I)‐catalyzed enantioselective 1,6‐borylation of α,β,γ,δ‐unsaturated phosphonates [9b] . In 2018, the Lam group found that both Z ‐allylic and E ‐allylic boronates can be obtained as the major product with high enantioselectivity, simply by tuning the reaction solvent and the concentration in the copper(I)‐catalyzed 1,6‐borylation of α,β,γ,δ‐unsaturated ketones [9c] …”
Section: Introductionmentioning
confidence: 99%